2020
DOI: 10.3390/s20205838
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of Impact-Echo Testing Data from a Fire-Damaged Reinforced Concrete Slab Using a Discrete Layered Concrete Damage Model

Abstract: The main objectives of this study are to investigate the spectral responses of a fire-damaged concrete slab using Impact-echo (IE) testing, and to develop a simplified model for interpreting the frequency shift due to heat-induced concrete damage after the fire. For these purposes, a reinforced concrete slab specimen (1000 mm (width) by 5000 mm (length) by 210 mm (thickness)) was fabricated in the laboratory. Heat damage in the concrete slab specimen was induced by exposing the bottom of the specimen to the te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Monte et al 21 used ground penetrating radar to study the development of water pore pressure in concrete subjected to heated temperature, which can result in the spalling of concrete. Ground penetrating radar has proven to be useful in detecting cracks or delamination in RC structures as studied by Miramini et al 22 , Lee et al 23 used the impact echo method to study heat-damaged slabs. The change in ultrasonic pulse velocity across the various depth of the slab can also predict the damage state.…”
Section: Introductionmentioning
confidence: 99%
“…Monte et al 21 used ground penetrating radar to study the development of water pore pressure in concrete subjected to heated temperature, which can result in the spalling of concrete. Ground penetrating radar has proven to be useful in detecting cracks or delamination in RC structures as studied by Miramini et al 22 , Lee et al 23 used the impact echo method to study heat-damaged slabs. The change in ultrasonic pulse velocity across the various depth of the slab can also predict the damage state.…”
Section: Introductionmentioning
confidence: 99%
“…The interpretation of non-propagating waves is an important process in IE data analysis. The fundamental thickness stretch mode normally dominates the spectral response of a plate if there are no near-surface defects, such as cracking, debonding, and honeycombs, in the concrete [13]. In the process of test and simulation detection, the predominant frequency detected in the middle of the column is the eigenvalue of the fundamental thickness stretch mode of the column.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier it has been shown that when Lamb waves are reflected from the edge of the plate, not only propagating waves are excited, but also evanescent waves that exist only near the edge of the plate [ 1 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. The existence of evanescent Lamb waves has been experimentally proven at free-edge boundaries [ 31 , 32 ], in phononic crystals [ 7 , 19 ], elastic metamaterial [ 18 ] and the possibility of their using for non-destructive control has been confirmed in [ 33 , 34 , 35 , 36 ]. These waves also could be used for development of a planar acoustic transducer for near field acoustic communication [ 37 ], passive pressure sensors for harsh-environment applications [ 38 ], new air-coupled ultrasonic for non-destructive techniques [ 39 ] and in acoustofluidic chips for microscale manipulation [ 40 ].…”
Section: Introductionmentioning
confidence: 99%